Environmental Systems Studies A Macroscope for Understanding and Operating Spaceship Earth - Imura, Hidefumi; SpringerLink (Online service) (Tokyo : Springer Japan : Imprint: Springer, 2013)
The environmental field is deep and wide. In the flood of information, how can people understand the underlying causes of what they hear about the environment from newspapers and television? This book was originally published in Japanese, with the aim of providing basic information about the ideas and methods to see and understand the interconnection between nature and human activities from a systematic point of view. The author subsequently prepared an English version of the same material for use as a textbook for the Global Environmental Leaders Program at Nagoya University, where he taught many students from Asia and Europe. The book covers diverse environmental issues such as climatic change, biodiversity preservation, energy conservation, and resource recycling. Readers can learn common methods of analysis and thinking to identify the core essence of economic and ecological interdependence, to look at problems from an overarching perspective, and to consider countermeasures to be taken. .
1. Seeing and Understanding Interactions between Nature and Humanity -- 2. Operating Our Spaceship Earth -- 3. Understanding the Global Climate System -- 4. Biodiversity and Ecosystem Service: Indicators of the Global Environment -- 5. An Evolutionary View of the Environment -- 6. Transforming Our Society: Low Carbon, Coexistence with Nature, and Sound Material Cycle -- 7. The Environment as a Commons: How Should It Be Managed? -- 8. Economics of the Environment -- 9. Resources, Energy, and Environmental Load -- 10. Japan and an Asian Perspective.
Keywords: Environmental management; Physical geography; Environmental economics; Environmental Management; Earth System Sciences; Environmental Economics